Spectrum of Urinary Tract Pathogens and their Antimicrobial Susceptibility Pattern in Paediatric patients - Aslam Chandio, Muhammad; Anwar, Tayyaba; Rehman, Anjum; Safdar, Saba; Salik Qasisarani; Saher Fatima; Zeeshan Ahmed; Ramina Shafique; Saleha Haider; Asna Shabbir (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To investigate the current spectrum and determine the age-related sensitivity or resistance patterns of bacterial uropathogens to commonly used antibiotics in children aged two months to twelve years. Methods: This cross-sectional study was carried out at the Pediatrics Department of Shaheed Mohtarma Benazir Bhutto Medical College (SMBBC) Lyari and Dr. Ziauddin Hospital Keamari, KDLB using a consecutive sampling technique from December 30th, 2022, until June1st, 2023. The diagnosis was based on a colony count of 105/ml of a single pathogen in a symptomatic child. Within 1 hour after the initial collection, samples were sent to the laboratory and were cultured in 5% sheep blood agar and MacConkey’s media. Results: Our study included 100 children with a “positive” urine culture, aged ranged from 2 months to 12 years. Thirty (30%) were males and seventy (70%) were females. E. coli was the most prevalent urinary pathogen, accounting for 52 (52%), followed by Klebsiella (29%), Proteus (9%), Pseudomonas (8%), and Enterococcus faecalis (2%). The majority of pathogens were sensitive to Amikacin, Imipenem, and Piperacillin/Tazobactam. Cefoperazon, Nitrofurantoin, and Ciprofloxacin were shown to be intermediately sensitive, whereas Amoxicillin-clavulanate, Ceftazidime, and Ceftriaxone were resistant. Conclusion:UTI is a source of morbidity in children, which requires regular studies to identify the organism and its sensitivity from time to time and recommend prompt empirical treatment to bring down the UTI-related morbidity and mortality in children.My study reflects a lack of in-vitro sensitivity to commonly used oral forms of antibiotics. Keywords: Spectrum, urinary pathogens, paediatric patients, urinary tract infection